Apoptosis induced by DICO, a novel non-aromatic B-ring flavonoid via a ROS-dependent mechanism in human colon cancer cells. Issue 23 (1st December 2022) - Wei, An-Hua; Zeng, Lu; Ruan, Jin-Lan; Zhou, Dao-Nian
Abstract: 5, 7-Dihydroxy-2-(1, 2-isopropyldioxy-4-oxo-cyclohex-5-enyl)-chromen-4-one (DICO) is a novel non-aromatic B-ring flavonoid, isolated mainly from Macrothelypteris viridifrons and has anti-tumour properties. In this study, we investigated the cytotoxicity and underlying biochemical pathways leading to cell death, in response to DICO treatment of a human colon cancer cell line HT-29. Our results indicated that DICO induced apoptosis by elevating the generation of reactive oxygen species, which could be quenched by the antioxidants N-acetyl cysteine. In addition, activation of signal transducer and activator of transcription 3 and suppression of nuclear factor kappa B played a crucial role in DICO-induced apoptosis. Overall, our results provide mechanistic insights into the apoptotic action of a potential anti-tumour drug, DICO. Graphical Abstract: UF0001